Beiträge zur Insektenfauna der DDR: Coleoptera - Eucinetidae. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1975)
Of the family Eucinetidae, so far only Eucinetus haemorrhous (Duftschmidt, 1812) has been established on the territory of the GDR. Two other species, Eucinetus caucasicus Reitter, 1885, and Eucinetus meridionalis Castelnau, 1836, may yet be found.